ANALYSIS OF THE MANAGEMENT OF A BRAZILIAN CONSTRUCTION COMPANY - Fonseca, Flávia Fernandes; Pereira, Ana Carolina Silva; Olivera, Ivna do Rosário; Oliveira, Luiz Augusto; Domingues, Paulo Lourenço (International Journal of Research -GRANTHAALAYAH, 2018)
The aim of the study was through a research of a company linked to the construction sector in Brazil; identify the strengths and weaknesses that the organization has. The subjects covered were: the company's goals, addressing how this works in relation to planning; the company management in order to demonstrate how it is performed its management in general and if it is done properly; legislation in which note the importance of compliance with laws within a company linked to the construction sector and finally, people management in which attempts to show how it is done within the organization and what are the improvements so that the company can best achieve the goals. Regarding methodology, directly applying questionnaire was used and interview with the owner of the organization. Thus, through the results and final discussions, it is important to note that many companies, large or small must be willing to always improve and innovate so that it has a differential in the market. Moreover, the importance of a link between all areas is great because through it, the company can improve its performance in a huge percentage.